Adsorption characteristics of reactive blue 81 by powdered activated carbon: Role of the calcium content. (August 2020) - Lv, Shuquan; Zhou, Zhiwei; Xue, Mengyuan; Zhang, Xiaohong; Yang, Zhu
Graphical abstract: Abstract: Adsorption by powdered activated carbon (PAC) is an efficient method for dye removal from wastewater, but the factors that influence it remain unclear. In our work, seven PACs having high performance of removal reactive blue 81 (RB 81) were screened among fourteen PACs, and three PACs showed better removal efficiency after modified with calcium. The adsorption kinetics of selected six PACs except PAC14 and modified PACs with calcium well fitted to pseudo-second-order. The isotherms of the screened PACs excluding PAC12 and PAC13 were well described by Langmuir mode dominated by monolayer adsorption. The correlation analysis indicated that contents of carbon, oxygen and chlorine, as well as Iodine number and methylene blue adsorption value of seven PACs were irrelevant to the adsorption capacity. BET surface area and total pore volume moderately correlated with absorption capacity. Sulphur (S) and calcium (Ca) content of PACs were significantly linear with the absorption capacity of PACs. The S and Ca elements in PAC had a crucial role in RB 81 adsorption, which can be taken as the priority indicators during the selection and optimization of PAC for RB 81 adsorption. This study provides support for the evaluation and optimization of the compatibility between the adsorption efficiency of different pollutants and PAC.